2018
DOI: 10.1007/s10967-018-6126-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and extraction of Am(VI) using a monoamidic extractant in 3D printed centrifugal contactors

Abstract: A series of tests were performed using centrifugal contactors to evaluate the separation of Am(VI) from cerium, as well as to determine the efficiency of the contactors. All experiments were performed using 2-cm, acrylic 3D-printed centrifugal contactors.Solvent extraction tests were performed using 1 M N,N-di(2-ethylhexyl)butyramide (DEHBA)/dodecane and a nitric acid feed solution spiked with 243 Am and 139 Ce and oxidized with 60 mg mL -1 sodium bismuthate. Approximately 72 % of the Am was extracted with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The electrode potentials of americium redox couples, as reported by Schulz and later by Silva et al, show that the electrochemistry of this actinide is very diverse in aqueous environments. , The Latimer diagram shows the stable trivalent cation may be oxidized to Am 4+ (−2.62 V vs SCE) to [Am V O 2 ] + (−1.727 V), and to [Am VI O 2 ] 2+ (−1.683 V) in 1.0 M HClO 4 ; however, the large reduction potentials demonstrate that access to the higher valence states requires powerful oxidizing agents. , Asprey et al used ammonium peroxydisulfate in HNO 3 and HClO 4 and confirmed the presence of hexavalent americium using spectroscopy. , Numerous studies followed, showing hexavalent accessibility with ozone (Ag + -catalyzed), sodium bismuthate, and copper periodate oxidants. However, the main limitations of the redox approach are the thermodynamic instability of AmO 2 2+ (because it undergoes autoreduction immediately upon formation), the low charge density ( z 2 / r ) of AmO 2 + , and the immediate reduction of Am 4+ back to Am 3+ via water oxidation. …”
Section: Introductionmentioning
confidence: 83%
“…The electrode potentials of americium redox couples, as reported by Schulz and later by Silva et al, show that the electrochemistry of this actinide is very diverse in aqueous environments. , The Latimer diagram shows the stable trivalent cation may be oxidized to Am 4+ (−2.62 V vs SCE) to [Am V O 2 ] + (−1.727 V), and to [Am VI O 2 ] 2+ (−1.683 V) in 1.0 M HClO 4 ; however, the large reduction potentials demonstrate that access to the higher valence states requires powerful oxidizing agents. , Asprey et al used ammonium peroxydisulfate in HNO 3 and HClO 4 and confirmed the presence of hexavalent americium using spectroscopy. , Numerous studies followed, showing hexavalent accessibility with ozone (Ag + -catalyzed), sodium bismuthate, and copper periodate oxidants. However, the main limitations of the redox approach are the thermodynamic instability of AmO 2 2+ (because it undergoes autoreduction immediately upon formation), the low charge density ( z 2 / r ) of AmO 2 + , and the immediate reduction of Am 4+ back to Am 3+ via water oxidation. …”
Section: Introductionmentioning
confidence: 83%
“…Both combined separation of Am and Cm from the HAR and separate Am and Cm management strategies are studied today. [9] Formerly elaborated methods for the Am/Cm separation can be grouped into three major categories: (1) selective oxidation of Am(III) to the tetra-or hexavalent state [10][11][12] ; (2) separation of Am(III) and Cm(III) with the use of two ligands with opposite solubility and selectivity with respect to Am(III) and Cm(III) and (3) methods based on the size-selective separation of these two ions from each other. Category (2) and (3) are described in more detail below.…”
Section: Introductionmentioning
confidence: 99%